2012
DOI: 10.1021/jz300639q
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Energy and Charge Transfer in Porphyrin Aggregate/Semiconductor (TiO2) Composites

Abstract: A porphyrin aggregate is reported that exhibits novel exciton state properties for light-harvesting applications. This porphyrin aggregate enables control of energy dissipation of coherent excited states by changing the self-assembly pattern. New exciton spectral features create a new route of energy transfer in this porphyrin aggregate. The kinetic model of exciton state decay is addressed in this Perspective by reporting steady-state and transient emission and absorption studies of porphyrin J- and H-aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 53 publications
3
111
0
1
Order By: Relevance
“…The molecules in J-aggregates are retained in the direction parallel to their molecular planes (nematic director of liquid crystal), whereas the direction of Haggregation is perpendicular to molecular planes, i.e., corresponding to "face-to-face" orientation (π-π stacking) of aromatic or hetero-rings. Some cyanines [34] and porphyrines [56] exhibit both J-and H-band on aggregation as it is shown in Figure 13.…”
Section: Page 8 Of 31mentioning
confidence: 88%
See 2 more Smart Citations
“…The molecules in J-aggregates are retained in the direction parallel to their molecular planes (nematic director of liquid crystal), whereas the direction of Haggregation is perpendicular to molecular planes, i.e., corresponding to "face-to-face" orientation (π-π stacking) of aromatic or hetero-rings. Some cyanines [34] and porphyrines [56] exhibit both J-and H-band on aggregation as it is shown in Figure 13.…”
Section: Page 8 Of 31mentioning
confidence: 88%
“…In contrast to J-aggregates manifesting strong long-wavelength absorption and resonant light emission missing in the molecularly-dispersed or solid-state dyes, the hypsochromic shift in absorption spectra and the absence of the photoluminescence are characteristic for so-called H-aggregation [53][54][55][56]. The molecules in J-aggregates are retained in the direction parallel to their molecular planes (nematic director of liquid crystal), whereas the direction of Haggregation is perpendicular to molecular planes, i.e., corresponding to "face-to-face" orientation (π-π stacking) of aromatic or hetero-rings.…”
Section: Page 8 Of 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Many organic compounds with covalently linked donor and acceptor moiety have been designed and synthesized for the purpose of revealing the origin of PET process [7][8][9]. At the same time, mimicking the natural PET with non-covalently systems based on varies of supramolecular interactions has also gained much attention in the past several decades [10,11]. In these supramolecular systems, electron donors and acceptors selfassemble into complexes, which offer the place for the PET process.…”
Section: Introductionmentioning
confidence: 99%
“…A range of porphyrins have been found to form nanorod like structures for example Reddy et al [27] demonstrated that H 2 TPP in acidic environments forms well defined nanorods assigned to occur due to J-aggregation. In porphyrins the formation of J aggregates are reported to result in a red-shift in absorption bands [30][31][32].…”
Section: Introductionmentioning
confidence: 99%